2023
DOI: 10.1007/s40279-023-01904-2
|View full text |Cite
|
Sign up to set email alerts
|

A Conceptual Exploration of Hamstring Muscle–Tendon Functioning during the Late-Swing Phase of Sprinting: The Importance of Evidence-Based Hamstring Training Frameworks

Judd T. Kalkhoven,
Mathias Lukauskis-Carvajal,
Deborah L. Sides
et al.

Abstract: An eccentrically lengthening, energy-absorbing, brake-driven model of hamstring function during the late-swing phase of sprinting has been widely touted within the existing literature. In contrast, an isometrically contracting, spring-driven model of hamstring function has recently been proposed. This theory has gained substantial traction within the applied sporting world, influencing understandings of hamstring function while sprinting, as well as the development and adoption of certain types of hamstring-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 204 publications
0
0
0
Order By: Relevance
“…Group A from the third day onwards, technical training through sprints was introduced, with feedback provided by a coach. The sports physiotherapist present on the field led the identification of predisposing factors such as forward lean [ 5 ], spine or sacroiliac joint pathologies [ 14 - 16 ], flexibility in the hamstring and lumbopelvic complex [ 17 - 20 ], and poor conditioning, overtraining, undertraining, excessive stretching, and muscle imbalances [ 19 , 21 - 24 ]. Strength training was included based on training blocks/phases to maintain conditioning.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Group A from the third day onwards, technical training through sprints was introduced, with feedback provided by a coach. The sports physiotherapist present on the field led the identification of predisposing factors such as forward lean [ 5 ], spine or sacroiliac joint pathologies [ 14 - 16 ], flexibility in the hamstring and lumbopelvic complex [ 17 - 20 ], and poor conditioning, overtraining, undertraining, excessive stretching, and muscle imbalances [ 19 , 21 - 24 ]. Strength training was included based on training blocks/phases to maintain conditioning.…”
Section: Methodsmentioning
confidence: 99%
“…A forward lean during sprinting has also been identified as a risk factor for hamstring injury [ 5 ], while another study found that both the early stance and swing phases presented as equal risk factors for injury [ 13 ]. Few other predisposing factors for hamstring injuries in sprinting have also been studied which include lumbar spine or sacroiliac joint pathologies without neural issues [ 14 - 16 ], lack of flexibility in the hamstring and lumbopelvic complex [ 17 - 20 ], poor conditioning, overtraining, undertraining, excessive stretching, and muscle imbalances [ 19 , 21 - 24 ].…”
Section: Introductionmentioning
confidence: 99%